Beyond Rivalry: Lessons from China–India Trade For Pakistan–India Relations through Economic and Media Engagement - Dr. Syed Shuja Uddin; Dr. Syed Shoaib Hussain; Shafiq-un-Nisa; Naseem Madad Ali (Journal of Religion and Society, 2025)
Owing to political rivalry, national security concerns, and the influence of hostile media narratives, relations between the two neighbors have become antagonistic. Meanwhile, the scenario of China-India relations is favorable despite having a long-standing territorial dispute. This eliminates the significance of economic bounds and good communication skills. The eye-opening lesson for Pakistan and India is to transcend zero-sum rivalry through economic engagement and the effective use of media diplomacy. Without a shadow of a doubt, there is distrust between Beijing and New Delhi, but they know the value of trade and a peaceful environment in the region. The same pattern can apply to the India and Pakistan case. These two neighbors can play such a vital role in the region. Through the media, construct new and peaceful approaches for future minds. Indeed, the press is a powerful way to connect people-to-people. Media can be utilized as a wonderful instrument to create a national agenda, build trust, and erode envy. This paper elaborates on the influence of media and economic engagement. In the current situation, the media of both countries play a negative role. The media often provokes the public against each other and spreads enmity. However, positive initiatives through the media can not only connect people-to-people but also encourage leaders to move toward a path of development. This article critically analyzes the comparison between China-India relations vs. India-Pakistan relations under the lens of the constructivism approach. Further, for accumulating historical data, quantitative and qualitative methods are used. Keywords: Pakistan–India Relations, China–India Trade, Economic Diplomacy, Media Engagement, Regional Cooperation, Interdependence, Peacebuilding